Reconstructing a Longitudinal Dataset for Tasmania - Trudy Cowley; Lucy Frost; Kris Inwood; Rebecca Kippen; Hamish Maxwell-Stewart; Monika Schwarz; John Shepherd; Richard Tuffin; Mark Williams; John Wilson; Paul Wilson (Historical Life Course Studies)
This article describes the formation of The Tasmanian Historical Dataset a longitudinal data resource spanning the 19th and early 20th century. This resource contains over 1.6 million records drawn from digitised prison and hospital admission registers, military enlistment papers, births, deaths and marriages, census and muster records, arrival and departure lists, bank accounts and property valuations, maps and plans and meteorological observations. As well as providing an account of the many different sources that have been digitised coded and linked as part of this initiative, the article outlines current and past research uses to which this data has been put. Further information on tables and key variables is provided in an appendix.